Droplet Spectra and Drift Potential Generated by Flat-Fan Nozzles Spraying New Formulations of 2,4-D Engineered for Drift Reduction - Antuniassi, Ulisses R. [UNESP]; Moreira, Caio A. F. [UNESP]; Chechetto, Rodolfo G.; Pinheiro, Ana Cristina T. C.; Lucio, Felipe R.; Fritz, B. K.; Butts, T. R. (Astm International, 2018)
The aim of this work was to analyze the effect of spray solutions containing new formulations of 2,4-D choline salt (Enlist (TM) with Colex-D (TM) and Enlist Duo (TM) with Colex-D) on the droplet spectra and drift potential generated by flat-fan nozzles. The experimental design included comparisons between solutions with a single herbicide in it: 2,4-D dimethylamine salt (DMA (TM) 806 BR) and 2,4-D choline salt (Enlist with Colex-D). We also compared the premix of 2,4-D choline salt and glyphosate dimethylamine salt (Enlist Duo Colex-D) with tank mixtures of the 2,4-D dimethylamine salt with three different formulations of glyphosate (Glizmax Prime, Roundup Transorb R, and Zapp QI). Labeled rates of the herbicides were diluted to 80 L ha land sprayed with flat-fan nozzles at 2.8 bar (Teejet XR11002 and AIXR11002). The volume median diameter and the percentage of droplets smaller than 105 p.m (V105) were obtained using an online particle-size analysis system. The drift index was calculated based on data collected in a wind tunnel at a wind speed of 2.5 m s-1. The amount of drift deposited on nylon strings at 2 m downwind from the nozzle was converted to a percentage of the total volume of spray solution sprayed on each replication. The results showed that the new formulation of 2,4-D choline salt engineered for drift reduction (Enlist Colex-D) provided lower drift potential based on both the droplet spectra and the wind tunnel data compared to the standard 2,4-D dimethylamine salt. The same result was found when comparing the premix of 2,4-D choline salt and glyphosate dimethylamine salt with tank mixtures of 2,4-D dimethylamine salt with glyphosate, regardless of whether glyphosate formulation was part of the tank mixture.
Keywords: glyphosate; 2,4-D choline salt; formulations; wind tunnel; nozzles